2010
DOI: 10.1146/annurev.publhealth.012809.103701
|View full text |Cite
|
Sign up to set email alerts
|

Confronting a Neglected Epidemic: Tobacco Cessation for Persons with Mental Illnesses and Substance Abuse Problems

Abstract: Tobacco use exerts a huge toll on persons with mental illnesses and substance abuse disorders, accounting for 200,000 of the annual 443,000 annual tobacco-related deaths in the United States. Persons with chronic mental illness die 25 years earlier than the general population does, and smoking is the major contributor to that premature mortality. This population consumes 44% of all cigarettes, reflecting very high prevalence rates plus heavy smoking by users. The pattern reflects a combination of biological, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
310
1
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(333 citation statements)
references
References 108 publications
(112 reference statements)
5
310
1
17
Order By: Relevance
“…This is important because these persons tend to be heavier smokers; and thus, the burden of morbidity and mortality may be more apparent in these smokers. 20,21 There are limitations to this paper. First, although we have a large sample size of over 16,000 Hispanic/Latino adults, our study is cross-sectional; and thus, cause-effect relationships cannot be established.…”
Section: Discussionmentioning
confidence: 96%
“…This is important because these persons tend to be heavier smokers; and thus, the burden of morbidity and mortality may be more apparent in these smokers. 20,21 There are limitations to this paper. First, although we have a large sample size of over 16,000 Hispanic/Latino adults, our study is cross-sectional; and thus, cause-effect relationships cannot be established.…”
Section: Discussionmentioning
confidence: 96%
“…Comorbid substance use disorders pose significant challenges to smoking cessation because the use of illicit substances may provide social cues to smoking and augment the pleasurable effects of nicotine. 33 Given these findings, there is mounting evidence for the integration of treatment for nicotine dependence with that of substance use treatment. 1,12,31,34 A meta-analysis showed that treating nicotine addiction during substance use treatment may enhance short-term smoking cessation and lead to prolonged abstinence from alcohol and other illicit substances.…”
Section: Discussionmentioning
confidence: 99%
“…[10,32] Literature in this area often makes the commonsense assumption that, since persons with mental illness both smoke at a higher rate and die sooner than the general population, smoking causes at least some excess mortality. [28][29][30][31][32] Oregon data do not support this conflation, since persons receiving mental health services did not die of tobacco-related deaths in greater proportion than the general population. Further research may confirm or disconfirm this finding but, until that time, caution is needed to interpret how higher smoking prevalence may be related to greater mortality among those with mental illness.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco-related deaths are often measured using mathematical models using ICD-9 or ICD-10 codes, reflecting cancers, cardiovascular disease, and other conditions or causes associated with tobacco use. Use of ICD-9 and ICD-10 codes have been criticized, however, as leading to under-estimates of tobacco-related deaths [31][32][33] and the CDC has recommended that physicians use specific mention of whether the death was tobacco-related in death certificates. This places the determination of tobacco-related death with the physician completing the death certificate, and enabling the physician to use any data available at the time of death concerning tobacco as a contributing factor.…”
Section: Methodsmentioning
confidence: 99%